Business Process Management Cases - Brocke, Jan vom; Mendling, Jan (Springer, 2018)
Business Process Management (BPM) is an important and timely topic. For many companies, BPM is the key for mastering digital transformation and for innovating their business models. The fast pace of change has also taken a grip on concepts and techniques of BPM, with various new ideas emerging from research and practice. Several excellent sources exist that summarize established concepts of BPM. So far, however, a collection of real-world cases making available the experience of organizations applying BPM for various objectives was missing. It is the aim of this book to close this gap and to increase knowledge exchange based on real-world BPM projects for fostering both BPM education and practice. For this book, we have gathered 31 cases on how companies use business process management to achieve outstanding operational results. Each of these cases is organized according to a uniform structure including the following parts: • Introduction—What is the story of the case? The authors give a brief narrative of the entire story to grasp your interest in the case. This part includes a summary of the key figures of the company. • Situation faced—What was the initial problem situation? What situation led to the action taken? The authors specify the context of the case as to needs, constraints, incidents, objectives, and beyond. • Action taken—What has been done? What measures have been taken, as e.g. regarding the process redesign or process innovation? Which methods and approaches have been used? The authors provide a factual passage of the course of events. • Results achieved—What effects could be observed resulting from the action taken? This could be changes in performance measures as well as qualitative statements from employees, customers, or other business partners. Here, the authors also discuss how far expected results materialize and how far expectations were met or not met. • Lessons learned—Reflecting the overall case, what can others learn from it? The authors derive around five lessons learned, which are grounded in the case and which are interesting for others to take as an example. The cases of this book are grouped into four major blocks, which are inspired by the six core elements of BPM by de Bruin and Rosemann. Part I contains cases that relate to strategy and governance. The cases stem from SAP in Germany, S-Y Systems Technologies in Germany, Autogrill in Italy, the Dompe eHospital in Sri Lanka, a leading telecommunications provider in the Middle East, and the Slovene public service company Snaga. Part II presents cases on BPM methods. These cases relate to “Die Mobiliar” from Switzerland, Queensland University of Technology in Australia, the City of Ghent in Belgium, a Brazilian insurance company, the telecommunications provider 3 in Germany, Bolzano Hospital in Italy, an Australian insurance company, Software AG in Germany, and St. Andrew’s War Memorial Hospital in Australia. Part III discusses cases on information technology and BPM. The cases refer to CrowdStrom in Germany, MELOS in Germany, Deutsche Bank in Germany, BRFkredit in Denmark, a German manufacturing company, Zalando in Germany, Adler Moden in Germany, a Slovak logistics provider, and HEYCO-WERK in Germany. Part IV discusses BPM-related issues of people and culture. It builds on cases from Lufthansa Technik in Germany, 1&1 Internet in Germany, TCE-PE from Brazil, Jade University of Applied Science in Germany, and a Norwegian company in the Oil and Gas sector.
Digital Innovation and Business Transformation in Practice